2021
DOI: 10.1001/jamanetworkopen.2021.11797
|View full text |Cite
|
Sign up to set email alerts
|

Medicare Support for Dental and Podiatry Graduate Medical Education Programs

Abstract: IMPORTANCE Oral health care faces ongoing workforce challenges that affect patient access and outcomes. While the Medicare program provides an estimated $14.6 billion annually in graduate medical education (GME) payments to teaching hospitals, including explicit support for dental and podiatry programs, little is known about the level or distribution of this public investment in the oral health and podiatry workforce.OBJECTIVE To examine Medicare GME payments to teaching hospitals for dental and podiatry resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…This is also consistent with a recent study that measured the effect of HRSA dental training grants on dentists’ practice locations in the US, which found that HRSA funding increases the likelihood that a dentist will practice in a rural area, improving access to and delivery of oral health care services to rural populations 2 . Similarly, GME funding, while not applicable for all types of PGD programs, is a significant investment in the development and support of PGD programs and institutions 11 . We find that individuals who currently practice in a state with higher investment in GME have higher odds of having PGD training.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This is also consistent with a recent study that measured the effect of HRSA dental training grants on dentists’ practice locations in the US, which found that HRSA funding increases the likelihood that a dentist will practice in a rural area, improving access to and delivery of oral health care services to rural populations 2 . Similarly, GME funding, while not applicable for all types of PGD programs, is a significant investment in the development and support of PGD programs and institutions 11 . We find that individuals who currently practice in a state with higher investment in GME have higher odds of having PGD training.…”
Section: Discussionsupporting
confidence: 87%
“…2 Similarly, GME funding, while not applicable for all types of PGD programs, is a significant investment in the development and support of PGD programs and institutions. 11 We find that individuals who currently practice in a state with higher investment in GME have higher odds of having PGD training. If we assume residents may be likely to remain in the state where they had their terminal training, this is not surprising, but much more research is necessary to understand the impact of dental GME funds.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…We used a curated database of graduate medical education (GME) funding data from the Centers for Medicare and Medicaid Services, 17 dental residency program data from the 2018–2019 ADA Survey of Advanced Dental Education, 15 and podiatric residency program data from the Central Application Service for Podiatric Residencies 18 to estimate the amount of GME funding per dental residency slot each state received in 2018. GME funding for dental residency training is bundled together with funding for podiatric medicine residency programs; how much money was allocated to each type of program in 2018 was unknown.…”
Section: Methodsmentioning
confidence: 99%